Eco-Friendly, Simple, Fast, and Sensitive UPLC-MS/MS Method for Determination of Pexidartinib in Plasma and Its Application to Metabolic Stability - Essam Ezzeldin; Muzaffar Iqbal; Yousif A. Asiri; Gamal A. E. Mostafa; Ahmed Y. A. Sayed (Molecules, 2022)
Pexidartinib is the first drug approved by the U.S. Food and Drug Administration specifically to treat the rare joint tumor tenosynovial giant cell tumor. In the current study, a validated, selective, and sensitive UPLC-MS/MS assay was developed for the quantitative determination of pexidartinib in plasma samples using gifitinib as an internal standard (IS). Pexidartinib and IS were extracted by liquid-liquid extraction using methyl tert-butyl ether and separated on an acquity BEH C18 column kept at 40 °C using a mobile phase of 0.1% formic acid in acetonitrile: 0.1% formic acid in de-ionized water (70:30). The flow rate was 0.25 mL/min. Multiple reaction monitoring (MRM) was operated in electrospray (ESI)-positive mode at the ion transition of 418.06 > 165.0 for the analyte and 447.09 > 128.0 for the IS. FDA guidance for bioanalytical method validation was followed in method validation. The linearity of the established UPLC-MS/MS assay ranged from 0.5 to 1000 ng/mL with r > 0.999 with a limit of quantitation of 0.5 ng/mL. Moreover, the metabolic stability of pexidartinib in liver microsomes was estimated.